Rapid electron microscopy in oncology. Issue 1 (January 1977) - Carr, I; Toner, P G
Abstract : The case is argued for wider use of electron microscopy as an aid to histological diagnosis in problem cases such as tumours of uncertain histogenesis. In practical terms, electron microscopy can produce results as "immediate" as many special stains in regular use. The cost of providing an effective service can be favourably compared with that of various other diagnostic aids commonly called upon in normal clinical practice. It is suggested that exploitation of this growth area of morphological pathology will enhance the attractions of the discipline of histopathology to talented potential recruits.